Increased hemoglobin mass and VO2max with 10 h nightly simulated altitude at 3000 m - Neya, M.; Enoki, T.; Ohiwa, N.; Kawahara, T.; Gore, C. J. (International Journal of Sports Physiology and Performance, 2013)
Purpose: To quantify the changes of hemoglobin mass (Hbmass) and maximum oxygen consumption (VO2max) after 22 days training at 1300-1800 m combined with nightly exposure to 3000-m simulated altitude. We hypothesized that with simulated 3000-m altitude, an adequate beneficial dose could be as little as 10 h/24 h. Methods: Fourteen male collegiate runners were equally divided into 2 groups: altitude (ALT) and control (CON). Both groups spent 22 days at 1300-1800 m. ALT spent 10 h/night for 21 nights in simulated altitude (3000 m), and CON stayed at 1300 m. VO2max and Hbmass were measured twice before and once after the intervention. Blood was collected for assessment of percent reticulocytes (%retics), serum erythropoietin (EPO), ferritin, and soluble transferrin receptor (sTfR) concentrations. Results: Compared with CON there was an almost certain increase in absolute VO2max (8.6%, 90% confidence interval 4.8-12.6%) and a likely increase in absolute Hbmass (3.5%; 0.9-6.2%) at postintervention. The %retics were at least very likely higher in ALT than in CON throughout the 21 nights, and sTfR was also very likely higher in the ALT group until day 17. EPO of ALT was likely higher than that of CON on days 1 and 5 at altitude, whereas serum ferritin was likely lower in ALT than CON for most of the intervention. Conclusions: Together the combination of the natural and simulated altitude was a sufficient total dose of hypoxia to increase both Hbmass and VO2max.